Implementation of the Repetitive Method in Improving Student Learning Outcomes in Islamic Religious Education Subjects - Taufik Hidayat; Harzen Septiawan; Hamdani Abdi (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2025)
Islamic Religious Education (PAI) learning in elementary schools requires appropriate methods so that students not only understand the material, but are also able to remember and practice it in everyday life. However, in practice, low student learning outcomes are still found due to the lack of variety in learning methods and the minimal active involvement of students in the teaching and learning process. Therefore, it is necessary to apply learning methods that can increase student motivation and learning outcomes, one of which is through the Repetitive Method Learning Method. The purpose of this study is to describe: (1) the application of the Repetitive Method Learning Method, (2) the improvement of student learning outcomes in PAI subjects at SDN 12 Kinali, and (3) supporting and inhibiting factors in the application of the Repetitive Method Learning Method in improving student learning outcomes in PAI subjects at SDN 12 Kinali. This study uses a descriptive approach with a qualitative field research type. The data sources in this study consist of primary data and secondary data obtained through interviews, observations, and documentation techniques directly in the field. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using data triangulation and source triangulation techniques to ensure data validity. The results of the study showed that: (1) the application of the Repetitive Method Learning Method in Islamic Religious Education learning at SDN 12 Kinali went well, marked by teacher readiness before the learning process, such as preparing lesson plans, student worksheets, and textbooks; (2) the use of the Repetitive Method Learning Method was able to increase student motivation and learning outcomes in Islamic Religious Education subjects; and (3) supporting factors for the application of this method include teacher commitment and teamwork, while the inhibiting factors were the lack of teamwork and low teacher commitment in implementing learning.